Pengaruh Perubahan Lahan, Tingkat Kemiskinan Dan Pendapatan Beberapa Sektor Perekonomian Terhadap Indeks Pembangunan Manusia : Studi Di Provinsi Lampung - Anisa Awalul Khoiriah; Samsul Bakri; Trio Santoso (Jurnal Sylva Lestari, 2017)
In each region that are transitioning from an agricultural economic activity to industrialeconomic activity has always faced deforestation or forest cover changes in LampungProvince. Changes in forest cover can affect the value of the Human Development Index(HDI). One of the cause of forest decline is a result of poverty sourced by low access to landresources. Furthermore, revenue in the sectors of the economy if hypothesized was alsoinfluenced by changes in the value of the HDI. This study aims to determine the impact ofchanges in forest cover and land, poverty, and income in the economic sectors of the IPM. This study was conducted in September 2015-January 2016, which consists of laboratoryactivity, namely the determination of land cover change in 2002, 2009, and 2013 throughprocessing of satellite imagery data and then continued with field checks. Data of the poverty,income in the economic sectors and IPM obtained through the acquisition of data from theBPS. Multiple linear regression modelling applied to the response variable HDI withexplanatory variables such as changes in forest cover and human welfare indicators.Optimization parameters used Minitab 11. The conclusions of the results of the regressionmodelling showed that the proportion of state forests(p value = 0,037), community forests(pvalue =0,009), fields(p value = 0,040), open land(p value = 0,307), poverty kemiskinan (pvalue = 0,595), disadvantaged families(p value = 0,034)and economic growth(p value =0,146)could decrease the performance of HDI next two years. While the land up(p value =0,675), GDP in the transport sector(p value = 0,002), communications(p value = 0,071),services sector(p value = 0,067)and in others(p value = 0,066)can markedly increase thenumber IPM in Lampung province.